Strategies for attraction and retention of health workers in remote and difficult-to-access areas of Chhattisgarh, India: Do they work? - Suchitra Lisam; Sulakshana Nandi; Kanica Kanungo; Prem Verma; Jay Prakash Mishra; Dilip Singh Mairembam (Wolters Kluwer Medknow Publications, 2015)
Background: To address the acute shortages of health workers in underserved, remote, and difficult-to-access areas, the Government of Chhattisgarh and the National Rural Health Mission (NRHM) launched the Chhattisgarh Rural Medical Corps (CRMC) in 2009. CRMC has enabled provisions such as financial incentives, residential accommodation, life insurance, and extra marks during admission at the postgraduate (PG) level to eligible doctors for the attraction and retention of health workers, i.e., doctors, staff nurses, auxiliary nurse midwives (ANMs), and rural medical assistants (RMAs) in underserved areas. Objectives: This study aims to understand the CRMC scheme in terms of implementation, challenges, gaps, and outcome in achieving the attraction and retention of health workers in the remote and difficult-to-access areas of Chhattisgarh. Materials and Methods: The study adopts a mix of both qualitative and quantitative research methods. The purposive sampling method was used for the selection of three districts having normal, difficult, and inaccessible areas. Data were collected through key informant (KI) interviews with beneficiaries and non-beneficiaries of CRMC or district and state government officials, and reviews of document were analyzed using a thematic analysis approach. Results: CRMC has made positive outcome as 1319 health workers, including doctors, have joined the service in 2010-11, reducing the vacancy of doctors from 90% to 45%. The scope of CRMC was primarily limited to payment of monthly financial incentives. The fund utilization rate of CRMC has increased (from 27% in 2009-10 to 98% in 2011-12), though there are delays in payment of incentives. The majority of staff lack awareness about CRMC during job applications. The payment of incentives based on facility performance has demotivated staff. Conclusions: Establishment of a performance management system, activating the CRMC cell to make it functional, and wide publicity of CRMC benefits are likely to improve attraction and retention of staff.